2023
DOI: 10.3390/ijms241713320
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Urban Particulate Matter-Induced Airway Inflammation by RIPK3 through the Regulation of Tight Junction Protein Production

Sun-Hee Park,
Hyun-Chae Lee,
Hye Min Jeong
et al.

Abstract: Urban particulate matter (UPM) is a high-hazard cause of various diseases in humans, including in the respiratory tract, skin, heart, and even brain. Unfortunately, there is no established treatment for the damage caused by UPM in the respiratory epithelium. In addition, although RIPK3 is known to induce necroptosis, its intracellular role as a negative regulator in human lungs and bronchial epithelia remains unclear. Here, the endogenous expression of RIPK3 was significantly decreased 6 h after exposure to UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The necrosome recruits and phosphorylates the mixed lineage kinase domain-like protein (MLKL), which oligomerizes and induces necroptosis at the cell membrane [15]. In some tumor entities, the gene is already considered a potential tumor suppressor gene and exhibits aberrant expression [16][17][18][19]. Geserick et al previously showed the loss of RIPK3 expression in malignant melanoma and the resulting necroptosis resistance [20].…”
Section: Introductionmentioning
confidence: 99%
“…The necrosome recruits and phosphorylates the mixed lineage kinase domain-like protein (MLKL), which oligomerizes and induces necroptosis at the cell membrane [15]. In some tumor entities, the gene is already considered a potential tumor suppressor gene and exhibits aberrant expression [16][17][18][19]. Geserick et al previously showed the loss of RIPK3 expression in malignant melanoma and the resulting necroptosis resistance [20].…”
Section: Introductionmentioning
confidence: 99%